The Green Industrial Revolution: Lessons from the history of past energy transitions - Alessio Terzi; Roger Fouquet (EconPol Forum, 2023)
The challenges associated with today's green transition echo dynamics during past energy revolutions. Improvements in energy efficiency and sobriety can be part of a decarbonization strategy but with muted impact. An effective and credible climate policy must be chiefly targeted at accelerating a Green Industrial Revolution. Governments have many tools to do so, including taxation, regulation, public investment, and industrial policy. Cushioning blows to income and consumption of low-income households will be important in avoiding social backlash, slowing decarbonization.
Keywords: 330